2022
DOI: 10.9734/csji/2022/v31i5820
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals and Total Hydrocarbon Contents of Nypa fruticans Grown along the Shores of Qua Iboe River, Akwa Ibom State of Nigeria

Abstract: This study ascertains the amount of heavy metal and hydrocarbon content in an area exposed to crude oil exploration and exploitation activities. The study area is the Qua Iboe River in the Niger Delta region of Nigeria and the study samples were Nypa palm (Nypa fruticans) leaves obtained along the shores of the river. The concentration of Pb, Cd, Cu and Ni in the leaves were determined using the Atomic Absorption Spectrophotometer while Total Hydrocarbon Content was determined using Gas Chromatography, coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 14 publications
4
4
0
Order By: Relevance
“…On the pH scale, pH of 7.0 indicates a neutral solution, pH values smaller than 7.0 indicate acidity, pH values larger than 7.0 indicate alkalinity. The mean levels of pH in this study were consistent with levels reported by [2,12] and agreed with standards of 6.5 -8.5 set up WHO, USPH and NSDWQ.…”
Section: Hydrogen Ion (Ph)supporting
confidence: 91%
See 4 more Smart Citations
“…On the pH scale, pH of 7.0 indicates a neutral solution, pH values smaller than 7.0 indicate acidity, pH values larger than 7.0 indicate alkalinity. The mean levels of pH in this study were consistent with levels reported by [2,12] and agreed with standards of 6.5 -8.5 set up WHO, USPH and NSDWQ.…”
Section: Hydrogen Ion (Ph)supporting
confidence: 91%
“…Comparatively, higher levels were recorded in dry season than wet season in all locations and could be ascribed to dilution and concentration effects of the volume of water in wet and dry seasons respectively. Levels recorded across all sampling locations were lower than levels reported by [10] but were consistent with levels reported by [12] In general, levels recorded in this study were below maximum limits of 250µS/cm recommended for drinking water by WHO and other regulatory bodies.…”
Section: Electrical Conductivity (Ec)supporting
confidence: 87%
See 3 more Smart Citations